Race predictors and hemodynamic alteration after an ultra-trail marathon race - Taksaudom N; Tongsiri N; Potikul A; Leampriboon C; Tantraworasin A; Chaiyasri A (Dove Medical Press, 2017)
Noppon Taksaudom,1 Natee Tongsiri,2 Amarit Potikul,1 Chawakorn Leampriboon,1 Apichat Tantraworasin,1 Anong Chaiyasri,1 1Cardiovascular and Thoracic Surgery Unit, Department of Surgery, Chiang Mai University Hospital, 2Department of Mathematics, Faculty of Science, Chiang Mai University, Chiang Mai, Thailand Objective: Unique rough-terrain ultra-trail running races have increased in popularity. Concerns regarding the suitability of the candidates make it difficult for organizers to manage safety regulations. The purpose of this study was to identify possible race predictors and assess hemodynamic change after long endurance races.Methods: We studied 228 runners who competed in a 66 km-trail running race. A questionnaire and noninvasive hemodynamic flow assessment including blood pressure, heart rate, stroke volume, stroke volume variation, systemic vascular resistance, cardiac index, and oxygen saturation were used to determine physiologic alterations and to identify finish predictors. One hundred and thirty volunteers completed the questionnaire, 126 participants had a prerace hemodynamic assessment, and 33 of these participants completed a postrace assessment after crossing the finish line. The participants were divided into a finisher group and a nonfinisher group.Results: The average age of all runners was 37 years (range of 24–56 years). Of the 228 runners, 163 (71.5%) were male. There were 189 (82.9%) finishers. Univariable analysis indicated that the finish predictors included male gender, longest distance ever run, faster running records, and lower diastolic pressure. Only a lower diastolic pressure was a significant predictor of race finishing (diastolic blood pressure 74–84 mmHg: adjusted odd ratio 3.81; 95% confidence interval [CI]  =1.09–13.27 and diastolic blood pressure <74 mmHg: adjusted odd ratio 7.74; 95% CI =1.57–38.21) using the figure from the multivariable analysis. Among the finisher group, hemodynamic parameters showed statistically significant differences with lower systolic blood pressure (135.9±14.8 mmHg vs 119.7±11.3 mmHg; p<0.001), faster heart rate (72.6±10.7 bpm vs 96.4±10.4 bpm; p<0.001), lower stroke volume (43.2±13.6 mL vs 29.3±10.1 mL; p<0.001), higher stroke volume variation; median (interquartile range) (36% [25%–58%] vs 53% [33%–78%]; p<0.001), and lower oxygen saturation (97.4%±1.0% vs 96.4%±1.0%; p<0.001). Systemic vascular resistance and cardian index did not change significantly. Conclusion: The only race finishing predictor from the multivariable analysis was lower diastolic pressure. Finishers seem to have a hypovolemic physiologic response and a lower level of oxygen saturation. Keywords: running, physical endurance, athletic injuries, sports, athletic performance